2016
DOI: 10.1177/0160017616650488
|View full text |Cite
|
Sign up to set email alerts
|

Are Rural Costs of Living Lower? Evidence from a Big Mac Index Approach

Abstract: Rural leaders can point to low housing costs as a reason that their area should be competitive for business attraction. To what extent do rural housing costs offset transportation and other locational disadvantages in cost structures? The United States lacks information to systematically answer the question. We adapt a strategy employed by The Economist in exploring purchasing power parity: the Big Mac index. We gather information on Big Mac prices with a random sample of restaurants across the contiguous Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…While rates of unaffordable housing in 2016 were at 25 percent in nonmetro counties, 26 percent in small metros, and 40 percent in large metros (Harvard JCHS 2018), differences in overall cost of living relative to income are much smaller between county types (Nord 2009). One study found that while large metro areas tend to be more costly there is little difference in costs of living between medium metros, small metros, and rural areas both near and far from metropolitan areas (Loveridge and Paredes 2018). For housing costs specifically, in the ten largest metro areas the median monthly housing costs exceeded $1,300, while costs in all other metros were around $700 and $650 for nonmetro counties (Harvard JCHS 2018).…”
Section: Longitudinal Change In Housing Costsmentioning
confidence: 99%
“…While rates of unaffordable housing in 2016 were at 25 percent in nonmetro counties, 26 percent in small metros, and 40 percent in large metros (Harvard JCHS 2018), differences in overall cost of living relative to income are much smaller between county types (Nord 2009). One study found that while large metro areas tend to be more costly there is little difference in costs of living between medium metros, small metros, and rural areas both near and far from metropolitan areas (Loveridge and Paredes 2018). For housing costs specifically, in the ten largest metro areas the median monthly housing costs exceeded $1,300, while costs in all other metros were around $700 and $650 for nonmetro counties (Harvard JCHS 2018).…”
Section: Longitudinal Change In Housing Costsmentioning
confidence: 99%
“…Daniele and Malanima (2017) demonstrate, using the Big Mac Index, that the dispersion in real wages across regions in Italy is minimal, although nominal wages could be vastly different. Using a similar approach, Loveridge and Paredes (2018) show that "(living) costs in a metro -adjacent county are not different than areas that are much more rural" in the United States.…”
Section: Why the Big Mac Index?mentioning
confidence: 99%
“…Another impact of cities on the development of rural communities is the rent of land (Thunen, 1826). Rural households and landowners have access to lower consumer prices and land rent than city residents, allowing a lower cost of living (Kurre, 2003;Loveridge and Paredes, 2016), and consequently a higher quality of life (Roback, 1982;Deller et al, 2001), which is also due to natural amenities such as open spaces (Klaiber and Phaneuf, 2009) or the access to services that nearby cities offer. Such price advantages in rural communities are widely exploited in urban processes, such as the relocation of the manufacturing industry (Lonsdale and Browning, 1971) and suburbanization (Lopez et al, 1988;Burchfield et al, 2006).…”
Section: Cities and The Development Of Rural Communitiesmentioning
confidence: 99%